Effects of Self-Esteem on Resilience and School Happiness of Korean Students Participating in School Sports Clubs - Song, Hohyuns; Song, Jihwan; Lee, Seungman (Journal of Engineering Education Transformations, 2021)
School students can gain various advantages such as self-esteem and resilience through sports activities. This study examined the effects of self-esteem on resilience and school happiness of School students participating in school sports clubs. We aimed to provide primary data on the role of school sports clubs in the promotion of school happiness and how they can be used for this purpose. Through convenience sampling, this research selected around 324 Korean School students (84 for a preliminary and 240 for a primary survey) participating in school sports clubs. For data analyses, we used frequency, reliability and validity tests, descriptive statistics, correlation analysis, and multiple regression analysis. Results were: First, there was a significant correlation between self-esteem, resilience, and school happiness; second, positive self-esteem had positive effects on all subfactors of resilience, and negative self-esteem had negative effects on these same subfactors; third, positive self-esteem had positive effects on all subfactors of school happiness, and negative self-esteem had negative effects on some subfactors (student-teacher relationship, environmental satisfaction, learning activity pleasure, and psychological stability). Therefore, the development of ways to expand school sports clubs may help enhancing School students' self-esteem. School students can gain various advantages such as self-esteem and resilience through sports activities. This study examined the effects of self-esteem on resilience and school happiness of School students participating in school sports clubs. We aimed to provide primary data on the role of school sports clubs in the promotion of school happiness and how they can be used for this purpose. Through convenience sampling, this research selected around 324 Korean School students (84 for a preliminary and 240 for a primary survey) participating in school sports clubs. For data analyses, we used frequency, reliability and validity tests, descriptive statistics, correlation analysis, and multiple regression analysis. Results were: First, there was a significant correlation between self-esteem, resilience, and school happiness; second, positive self-esteem had positive effects on all subfactors of resilience, and negative self-esteem had negative effects on these same subfactors; third, positive self-esteem had positive effects on all subfactors of school happiness, and negative self-esteem had negative effects on some subfactors (student-teacher relationship, environmental satisfaction, learning activity pleasure, and psychological stability). Therefore, the development of ways to expand school sports clubs may help enhancing School students' self-esteem and resilience, so that students, who spend most of their time in school, can feel happy in this daily recurring setting.